2023
DOI: 10.1111/iej.13989
|View full text |Cite
|
Sign up to set email alerts
|

Sensory nerves, but not sympathetic nerves, promote reparative dentine formation after dentine injury via CGRP‐mediated angiogenesis: An in vivo study

Chaoning Zhan,
Minchun Huang,
Junyang Chen
et al.

Abstract: AimDental pulp is richly innervated by nerve fibres, which are mainly involved in the sensation of pain. Aside from pain sensation, little is known regarding the role of dental innervation in reparative dentine formation. We herein generated a mouse model of experimental dentine injury to examine nerve sprouting within the odontoblast and subodontoblastic layers and investigated the potential effects of this innervation in reparative dentinogenesis.MethodologyMouse tooth cavity model (bur preparation + etching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A different group reported that CGRP inhibits mineralization [21]. It should be noted that these reports experimented directly on DPSCs, while we and others have shown an intimate, bi-directional communication between the DPSCs and trigeminal neurons [11,15,[22][23][24][25][26][27][28][29][30]. Interestingly, bone research has also found that sensory afferents assist bone healing via CGRP signaling.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…A different group reported that CGRP inhibits mineralization [21]. It should be noted that these reports experimented directly on DPSCs, while we and others have shown an intimate, bi-directional communication between the DPSCs and trigeminal neurons [11,15,[22][23][24][25][26][27][28][29][30]. Interestingly, bone research has also found that sensory afferents assist bone healing via CGRP signaling.…”
Section: Discussionmentioning
confidence: 76%
“…A shallow dentin injury without pulp exposure has been shown to initiate the expression of neurotrophic factors, such as nerve growth factors (NGF), by odontoblasts [5][6][7]. This triggers a neuroinflammatory response in which sensory afferents sprout and secrete CGRP [8,9] to activate odontogenic activities for dentin repair [11,14]. In this report, we sought to determine whether the signaling downstream of Tgfbr2 in the developing dental pulp mesenchyme also regulates reactionary dentinogenesis and odontoblast secretion of neurotrophic signals that promote axon sprouting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution and patterning of free sensory nerve endings within the pulp-dentin complex of a fully developed tooth is not static, but can dynamically remodel in response to injury or infection. CGRP+ sensory endings exhibit branch sprouting surrounding sites of pulp damage, although prolonged and extensive damage leads to eventual pruning and denervation at the damage site ( 48 , 87 ). Denervation by resection of the inferior alveolar nerve is shown to accelerate necrosis induced by pulp damage ( 88 ), suggesting that sensory fibers may contribute to pulp-dentin regeneration in response to injury.…”
Section: The Function Of Intradental Sensory Neuronsmentioning
confidence: 99%